Analysis of Hot-Carrier Degradation in Small and Large W/L n-Channel Transistors - E. Bendada; K. Raïs (Active and Passive Electronic Components)
Device degradation due to hot-carrier in n-channel HEXFETs is shown to be related to the device geometrical structure. The form of I-V characteristics of the body-drain junction is found dependent of the hot-carrier stressing and of the layer dimensions. A large increases of the ideality factor, of the reverse recombination current, and of the series resistance are shown to be more significant for small values of L and W. It is demonstrated that the degradation of parameters is mainly caused by the generation of interface traps.